Revision of Hygrochilus (Orchidaceae: Epidendroideae: Aeridinae) and a molecular phylogenetic analysis - Li, Ming-He; Zhang, Guo-Qiang; Liu, Zhong-Jian; Lan, Si-Ren (Phytotaxa, 2014)
Hygrochilus and Sedirea are genera of orchids with only three species endemic to Asia. An analysis of ITS and five plastid regions using parsimony, maximum likelihood, and Bayesian methods obtain clear evidence that Sedirea is nested within and should be considered synonymous with Hygrochilus. We adopt a broadly defined Hygrochilus characterized by possession of four pollinia. A new combination, namely, Hygrochilus japonica, and a new species, namely, Hygrochilus tsii (Orchidaceae: Epidedroideae: Aeridinae), are proposed.